Identification of QTLs Associated With Agronomic Traits in Tobacco via a Biparental Population and an Eight-Way MAGIC Population - Liu, Yutong; Yuan, Guangdi; Si, Huan; Sun, Ying; Jiang, Zipeng; Liu, Dan; Jiang, Caihong; Pan, Xuhao; Yang, Jun; Luo, Zhaopeng; Zhang, Jianfeng; Ren, Min; et al. (Frontiers in Plant Science, 2022)
The agronomic traits such as plant height (PH), leaf number (LN), leaf length (LL) and leaf width (LW) are important in tobacco (Nicotiana tabacum L.), which are closely related to yield and quality. To identify QTL associated with agronomic traits in tobacco, 209 recombinant inbred lines (RIL) and 537 muti-parent advanced generation intercross (MAGIC) lines were developed. The bi-parental RIL and MAGIC lines were genotyped by 430K single nucleotide polymorphism (SNP) chip assay and were evaluated repeatedly for agronomic traits under different conditions. Furthermore, a total of 43 QTL associated with agronomic traits were identified by combining linkage mapping (LM) and association mapping (AM) methods. Among them, three major QTL, named as qPH13-3, qPH17-1 and qLW20-1, were identified repeatedly across different conditions using different genetic populations. The candidate genes of these major QTL were predicted. And the validation and utilization of the major QTL qLW20-1 for improvement of leaf width in tobacco were carried out in this study. These results can be used in molecular marker-assisted selection (MAS) breeding for important agronomic traits in tobacco.